A novel octagonal slot circular compact ultrawideband antenna with detailed frequency and time-domain analysis - Satish Kumar Kannale; Nagashettappa Biradar (Institute of Advanced Engineering and Science, 2023)
With time, the device's reliance on wireless communication and its users grows tremendously. The ultrawideband (UWB) technology offers a 7.5 GHz uncontrolled bandwidth. Because it allows for larger data rates over a short distance, UWB technology is the current and future requirement of new generation mobile networks. As a result, a novel octagonal slot circular compact UWB antenna with detailed frequency and time-domain analysis is proposed in this research. Throughout the UWB range, the hexagonal-shaped circular radiator aids in reaching better S11 parameters (S11-10 dB). The modified trapezoidal like partial ground plane allows for a wide bandwidth. The proposed UWB antenna operates at frequencies ranging from 3.2 to 13.1 GHz, allowing for a bandwidth of 9.9 GHz and a fractional bandwidth of 121.4%. Voltage standing wave ratio (VSWR) is seen to be in the range of 1 to 2 throughout this UWB range. Throughout the operational bandwidth, the antenna's gain ranges from 2.8 to 4.1 dB. The suggested UWB antenna has the advantages of being small, having superior impedance matching, a simple design, and having a high gain, all of which can be used to deploy the antenna for the aforementioned purposes.